2000
DOI: 10.1161/01.str.31.7.1752
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Brain Injury After Transient Middle Cerebral Artery Occlusion in Neonatal Rats

Abstract: Background and Purpose-Stroke in preterm and term babies is common and results in significant morbidity. The vulnerability and pathophysiological mechanisms of neonatal cerebral ischemia-reperfusion may differ from those in the mature cerebral nervous system because of the immaturity of many receptor systems and differences in metabolism in neonatal brain. This study details the neuropathological sequelae of reperfusion-induced brain injury after transient middle cerebral artery (MCA) occlusion in the postnata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 56 publications
6
95
2
1
Order By: Relevance
“…ADC values remained stable during the study period in CTL, with values around 1 ϫ 10 Ϫ5 cm 2 /s (23,26,28). In HIϩVEH, ADC evolved from values near 50% of control when measured 24 h after HI, corresponding to a restricted water mobility because of the cytotoxic edema, to supranormal values at P14, corresponding to a mobility near to free water due to cell death (24,26) (Table 1).…”
Section: Resultsmentioning
confidence: 92%
“…ADC values remained stable during the study period in CTL, with values around 1 ϫ 10 Ϫ5 cm 2 /s (23,26,28). In HIϩVEH, ADC evolved from values near 50% of control when measured 24 h after HI, corresponding to a restricted water mobility because of the cytotoxic edema, to supranormal values at P14, corresponding to a mobility near to free water due to cell death (24,26) (Table 1).…”
Section: Resultsmentioning
confidence: 92%
“…Previous reports (9) have shown that there is white matter involvement in neonatal stroke that is difficult to delineate in the neonate using MRI. However, the tfMCAO model appeared to have less corpus callosum involvement than the RVM model (Figs.…”
Section: Discussionmentioning
confidence: 95%
“…Evolution of injury in adult stroke models involving MCAO is described as containing a central primarily necrotic core and potentially salvageable penumbral regions. Imaging of the evolution of such injury is well-described in adult stroke models (16) and more recently in newborns (9,17). Conversion of penumbral regions to irreversible injury is complex and multiple metabolic, inflammatory and apoptotic postreperfusion responses to injury have been described (18).…”
Section: Ischemic Injury In the Rat Pupmentioning
confidence: 99%
“…13,74,78,79 Figure 1B shows that diffusion-weighted MRI depicts expansion of tissue 'at risk' associated with longer MCAO duration. Other MRI modalities have been proven useful in determining the extent of microcirculatory disturbances during MCAO and after reperfusion (perfusion-sensitive MRI), 76 disruption of the blood-brain barrier (BBB) (Gd-enhanced T1W imaging), 76 elucidation of the evolving injury (T2W imaging), 56,73,80 and changes in brain connectivity after injury during the neonatal period (diffusion tensor imaging). 81 Studies in tMCAO and H-I models in neonatal rodents have shown that although the components of injury that induce cell death and brain injury are similar to those occurring in experimental models of preterm injury-excitotoxic, oxidant, and inflammatory components-the targeted cell populations and regions affected by cerebral hypoxia and ischemia are different.…”
Section: Animal Models and The Underlying Mechanisms Of Perinatal Artmentioning
confidence: 99%